Multilevel Engagements of Pharmacists During the COVID-19 Pandemic: The Way Forward - Mallhi, Tauqeer Hussain; Liaqat, Aroosa; Abid, Arooj; Khan, Yusra Habib; Alotaibi, Nasser Hadal; Alzarea, Abdulaziz Ibrahim; Tanveer, Nida; Khan, Tahir Mehmood (Frontiers in Public Health, 2020)
Severe acute respiratory syndrome caused by novel corona virus (SARS-CoV-2) was first reported in China in December 2019 which was later declared to be public health emergency of international concern by World Health Organization (WHO). This virus proved to be very contagious resulting in life threatening respiratory intricacies posing overall public health and governance challenges. Amid the corona virus pandemic the unprecedented increase in healthcare demands, only inventive and adaptive practice among healthcare professionals is the need of hour. Pharmacy services are an important mainstay in the public health and have considerable potential to combat COVID-19 pandemic. Pharmacists working in several localities and health facilities are linked to patients either directly or indirectly. They can act swiftly in public health response such as drafting professional service guidance to pharmacists working in various healthcare facilities, ensuring effective medicine supply system, monitoring and resolving drug shortage issues, establishing and promoting remote pharmacy services, counseling the public on infection prevention basics, educating about proper use of personal protective equipment, discouraging self-medication, participating in clinical trials, small scale manufacturing of sanitizers and disinfectants, busting the prevailing myths, conducting drug evaluation and active surveillance. These interventions will help ease unprecedented burden on healthcare facilities during ongoing pandemic and eventually will add value to patients and healthcare system. Current manuscript accentuates the potential roles and activities that pharmacists can initiate in various healthcare facilities to help in relieving pressure on overwhelmed healthcare system. The information and suggestions offered in this review could help in restructuring of existing pharmacy services by governments, public health bodies and policy makers in response to COVID-19 pandemic. Moreover, this manuscript will underscore any unrealized potential among pharmacists working in various sectors including community, hospital, industry and drug regulatory authorities.